2016
DOI: 10.1155/2016/6909085
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cefixime and Azithromycin Nanoparticles: An Attempt to Enhance Their Antimicrobial Activity and Dissolution Rate

Abstract: In this study cefixime and azithromycin nanoparticles were prepared by antisolvent precipitation with syringe pump (APSP) and evaporator precipitation nanosuspension (EPN) methods. The nanoparticles were characterized by XRD, FTIR, SEM, and TGA. X-ray diffraction pattern of cefixime samples showed the amorphous form, while azithromycin samples showed crystalline form. The FTIR spectra of parental drugs and synthesized nanoparticles have no major structural changes detected. The SEM images showed that nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…The vibrations at 1698 and 1683 cm −1 revealed the presence of amide I, resulted from the reaction of the carbonyl group and N–H bond, and a peak at 1338 cm −1 showed –OH vibrations in the samples [31, 40–42]. The development of new peaks related to Azy on the spectra of NMs indicated the successful conjugation of NMs [43].…”
Section: Resultsmentioning
confidence: 99%
“…The vibrations at 1698 and 1683 cm −1 revealed the presence of amide I, resulted from the reaction of the carbonyl group and N–H bond, and a peak at 1338 cm −1 showed –OH vibrations in the samples [31, 40–42]. The development of new peaks related to Azy on the spectra of NMs indicated the successful conjugation of NMs [43].…”
Section: Resultsmentioning
confidence: 99%
“…It can be correlated with the fact that the enhanced solubility of CA with resultant better diffusion achieved through CSD formulation attributed for significant difference in RZOI. Khan et al (2016) reported that, cefixime nanoparticles exhibited better antibacterial activity than pure cefixime against S. aureus and E. coli by agar well diffusion method [27]. Omolo et al (2018) demonstrated that antibacterial activities of different nanosuspension formulations of fusidic acid delivered through poloxamer 188 were found better as compared to pure fucidic acid [28].…”
Section: Discussionmentioning
confidence: 99%
“…They are very ready to focus on the medications to different indispensable organs by excellence of their submicron size or surface adjustments. 2,3…”
Section: Nanotechnology and Nanosuspensionmentioning
confidence: 99%